Biochemical profiling of metabolomics in heavy metal-intoxicated impaired metabolism and its amelioration using plant-based bioactive compound - Yaqoob, Azka; Rehman, Kanwal; Akash, Muhammad Sajid Hamid; Alvi, Maria; Shoaib, Syed Muhammad (Frontiers in Molecular Biosciences, 2022)
Exposure to Pb is widely spreading and has far-reaching negative effects on living systems. This study aimed to investigate the toxic effects of Pb, through biochemical profiling and the ameliorative effects of quercetin against Pb-toxicity. Twenty-five male Wistar albino mice were divided into the following five groups. The CON-group received normal saline; the Pb-group received PbAc; the Pb + Q-CRN group received lead acetate followed by quercetin; the Q-CRN group received quercetin; and the CRN group received corn oil. After 4 weeks, the mice were euthanized. It was speculated that Pb significantly increased the levels of serine, threonine, and asparagine and decreased the levels of valine, lysine, and glutamic acid in the plasma of Pb-group, thus impairing amino acid metabolism. However, in the Pb + Q-CRN group, the level of these six amino acids was restored significantly due to the ameliorative effect of quercetin. The presence of lipid metabolites (L-carnitine, sphinganine, phytosphingosine, and lysophosphatidylcholine) in mice serum was confirmed by ESI/MS. The GPx, SOD, GSH, and CAT levels were significantly decreased, and the MDA level was significantly increased, thus confirming the oxidative stress and lipid peroxidation in the Pb group. The antioxidant effect of quercetin was elucidated in the Pb + Q-CRN group. Expression of CPT-I, CPT-II, LCAT, CROT, CACT, and MTR genes was significantly upregulated in the liver of Pb goup mice. Hence, the findings of this study proved that Pb exposure induced oxidative stress, upregulated gene expression, and impaired the lipid and amino acid metabolism in mice.